The Liexi fauna: a new Lagerstätte from the Lower Ordovician of South China. Issue 1978 (13th July 2022) - Fang, Xiang; Mao, Yingyan; Liu, Qi; Yuan, Wenwei; Chen, Zhongyang; Wu, Rongchang; Li, Lixia; Zhang, Yuchen; Ma, Junye; Wang, Wenhui; Zhan, Renbin; Peng, Shanchi; et al.
Abstract : The Ordovician Lagerstätten record substantial amounts of excellent preservation and soft-bodied fossils during the Great Ordovician Biodiversification Event (GOBE). However, few Lagerstätten are known from the Lower Ordovician, most of which are preserved in restricted environments and high-latitude regions. Here, we report on a new tropical Lagerstätte, Liexi fauna, which has been recently discovered from a carbonate succession within the Lower Ordovician Madaoyu Formation in western Hunan, South China. It contains a variety of soft tissues, as well as rich shelly fossils, including palaeoscolecidan worms, possible Ottoia, trilobites, echinoderms, sponges, graptolites, polychaetes, bryozoans, conodonts and other fossils. The fauna includes taxa that are not only Cambrian relics, but also taxa originated during the Ordovician, constituting a complex and complete marine ecosystem. The coexistence of the Cambrian relics and Ordovician taxa reveals the critical transition between the Cambrian and Palaeozoic Evolutionary faunas. The unusual Liexi fauna provides new evidence for understanding Ordovician macroevolution and the onset of the GOBE.